2009
DOI: 10.1118/1.3176954
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo analysis of energy dependent anisotropy of bremsstrahlung x‐ray spectra

Abstract: The energy resolved emission angle dependence of x-ray spectra was analyzed by MCNPX (Monte Carlo N particle Monte Carlo) simulator. It was shown that the spectral photon flux had a maximum at a well-defined emission angle due to the anisotropy of the bremsstrahlung process. The higher the relative photon energy, the smaller the emission angle belonging to the maximum was. The trends predicted by the Monte Carlo simulations were experimentally verified. The Monte Carlo results were compared to both the Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Although the models above have been shown to be adequate for certain applications, their validity for off‐axis emissions has been challenged. Kákonyi et al 14 concluded that the emission angles predicted by Birch and Marshall, 7 and Poludniowski 8 disagree with MC predictions due to an inaccurate representation of the intrinsic bremsstrahlung angular distribution. A persistent assumption of x‐ray spectrum models has been that the angular distribution of bremsstrahlung production is uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Although the models above have been shown to be adequate for certain applications, their validity for off‐axis emissions has been challenged. Kákonyi et al 14 concluded that the emission angles predicted by Birch and Marshall, 7 and Poludniowski 8 disagree with MC predictions due to an inaccurate representation of the intrinsic bremsstrahlung angular distribution. A persistent assumption of x‐ray spectrum models has been that the angular distribution of bremsstrahlung production is uniform.…”
Section: Introductionmentioning
confidence: 99%
“…The physical background of the maximum in the spectral photon flux was discussed in our previous paper. 5 The position of the maximum of the spectral photon flux was shifted to higher emission angles with increased anode surface roughness in all energy ranges. The reduction of spectral photon flux due to anode surface roughness is higher at low emission angles.…”
Section: Iiib the Changes In The Spectra Shapementioning
confidence: 89%
“…The measured angular dependency of the detected intensity values also confirms the cylindrical symmetry of the x-ray beam. 5 The energy and angular distributions of the excited photons were recorded with resolutions of 0.5 keV and 1°, respectively, by means of transmitted image on cylinder ͑TIC͒ tally. 5 During simulations, no other variance reduction processes were applied; the default parametrization of MCNPX was used with the integrated TIGER series electron transport method.…”
Section: Iia Mcnpx Input Geometry and Parametrizationmentioning
confidence: 99%
See 2 more Smart Citations